Pendidikan Masyarakat Berbasis Andragogi dalam Pengembangan UMKM Kerupuk Rambak Ikan Lele - Nisa, Choirun; Prahastiwi, Eka Danik; Kisnawaty, Sudrajah Warajati; Cahyono, Dedi Dwi (Lembaga Yasin AlSys, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) based on local potential is a crucial strategy for improving the welfare of rural communities, including MSMEs producing kerupuk rambak catfish crackers managed by the Joint Business Group (Kelompok Usaha Bersama, KUB) Rukun Makmur in Sobo Village. However, limited knowledge and skills among business actors in production processes and business management remain the main constraints on their development. This community service activity aimed to strengthen the capacity of MSME actors through community education grounded in andragogy. The study employed a descriptive qualitative approach with a participatory design through training and production mentoring, with data collected via observation, interviews, and documentation. The results show that all participants were actively involved in the production process, most participants found it easier to understand production stages through hands-on practice, and there was an observable improvement in the neatness and uniformity of the kerupuk rambak catfish products. These findings indicate that an andragogical approach is effective in supporting contextual and applied adult learning and has the potential to serve as a sustainable community education–based assistance model for village MSMEs.